Molecular alterations in ependymomas - Biernat, Wojciech; Żawrocki, Antoni (Folia Neuropathologica, 2007)
Ependymal tumours are uncommon neoplasms of the central nervous system. Basic molecular alterations underlying their development are not so well defined in contrast to the astrocytic tumours. We compiled literature data on the molecular changes in ependymomas to show clinical and pathological correlations and review the prognostic factors that may much better predict their clinical behaviour.